The Postgraduate Learning Experience: The Impact of Information and Communication Technologies on Student Satisfaction and Degree Completion - Weyer, Birgit; Johnson, Tammy McClanahan (Proceedings of the International Conference on Networked Learning, 2006)
This study provided new knowledge in understanding how the online learning (OL) (N=22) postgraduate environment differed in program satisfaction and completion rates from the traditional learning (TL) (N=18) postgraduate environment. The key findings derived from this study were: (a) There was no evidence to support that individuals who graduated from online postgraduate programs had any difference in satisfaction levels with their program than those individuals who completed TL postgraduate programs; and (b) The estimated completion rate of individuals participating in the survey indicated that individuals studying in OL postgraduate programs completed their programs at a lower rate than individuals who studied in TL postgraduate programs.